Rekomendasi Peningkatan Layanan Okejek dengan Root Cause Analysis berdasarkan Hasil Analisis Sentimen Ulasan Pengguna - Andhika Mifta Alauddin; Nanang Yudi Setiawan; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
PT. Okejek Kreasi Indonesia is one of the company that engaged in the field of online transportation with it's flagship product, Okejek. However, Okejek still unable to compete with the giants in the field of online transportation. To find out the main causes of these problems, one way that can be done is by using sentiment analysis. Therefore, a sentiment analysis using 1890 data from user reviews on Google Play Store is performed. By using Recurrent Neural Network algorithm, an accuracy value and F1 score of 96% is obtained. After the sentiment analysis was successfully carried out, it is followed by Root Cause Analysis that based on 3 aspects which are service, price, and staff aspects. From these 3 aspects, the main problem were found to be a problem in the application, driver-partner's behavior, and the existing payment system. Therefore, a joint recommendation were made with stakeholders which resulted in the form of solutions that are improving applications, tightening SOPs, and also improving payment services.